Características clínicas de uma população com migrânea e tontura e resposta ao tratamento profilático após três e seis meses - Costa, Aline Turbino Neves Martins Da [UNIFESP] (2019)
A retrospective study carried out in the headache sector at the Migraine Clinic and University of the Federal University of São Paulo, through the review of patient charts from the outpatient clinic, attended from January 2014 to June 2016, in order to evaluate the clinical characteristics of patients, an aura presence associated with vertigo and / or non-vertiginous dizziness, as well as the efficacy of treatment at 3 months 6 months. In patients with a diagnosis of migrânea associated with vestibular symptoms, a presence of aura for the most prevalent subtype, being an average frequency of days of headache / month compatible with chronic migraine (pain more than 15 days in the month). Patients with migraine presented mostly vertigo, but an occurrence of dizziness combined with non-vertigo dizziness was also found verified. It was possible to observe that some otovestibular symptoms such as tinnitus, aural fullness, dizziness associated with dizziness, phonophobia, nausea, vomiting, osmophobia and kinesiophobia had a higher relative risk of occurrence in migraine with aura. Therapeutic therapies for vestibular migrans (MV), the outlets are direct from the treatment of migration, through studies comparing patients with MV, with the treatment with profile. In this group of patients with health problems, intensity and frequency of episodic dizziness / vertigo, as well as their associated characteristics, with time effect (the longer the treatment time the greater the improvement of symptoms) for improvement of pain and vestibular symptoms and without statistical classification of response between classes of medications choices for their treatment.